2017
DOI: 10.1108/ec-12-2015-0383
|View full text |Cite
|
Sign up to set email alerts
|

Pressure fluctuation characteristics in the sidewall gaps of a centrifugal dredging pump

Abstract: Purpose The purpose of this paper is to study the pressure fluctuation characteristics in the sidewall gaps of a centrifugal dredging pump in detail and discover the excitation sources. Design/methodology/approach An unsteady numerical simulation with shear–stress transport–scale-adaptive simulation (SAS-SST) model was conducted for a centrifugal pump considering the sidewall gaps. The numerical codes were validated by a model test carried out in China Water Resources Beifang Investigation, Design and Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…e pressure fluctuations at the top dead centre of the volute provide a better indication than at the discharge [6]. e radial and axial distributions of the fluctuation characteristics at the gap of the pump are analyzed, and the maximum pressure fluctuation occurs at the blade front side [7]. e pressure fluctuations in the impeller inlet show more complication in part flow conditions than at the best efficiency point [8].…”
Section: Introductionmentioning
confidence: 99%
“…e pressure fluctuations at the top dead centre of the volute provide a better indication than at the discharge [6]. e radial and axial distributions of the fluctuation characteristics at the gap of the pump are analyzed, and the maximum pressure fluctuation occurs at the blade front side [7]. e pressure fluctuations in the impeller inlet show more complication in part flow conditions than at the best efficiency point [8].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of centrifugal pumps are being used for slurry pipeline transportation systems. Erosion is a common problem for these pumps, which often leads to a reduction of the hydraulic performance, an increase in the noise and vibration level, and even worse, sometimes failure of the pumps [3,4]. The failure not only leads to the replacement of the defective parts but may also cause the shutdown of the whole transportation system.…”
Section: Introductionmentioning
confidence: 99%
“…For all kinds of flows inside the pump, the leakage flow from the impeller clearances can have a considerable effect on the pump performance [5][6][7]. Cao et al [2,3] have numerically investigated the pressure fluctuations for the leakage flow inside a centrifugal pump and found that the interaction between the main flow and leakage flow is strong and cannot be neglected. Furthermore, with the variation of the axial clearances, the main flow characteristic can be greatly affected.…”
Section: Introductionmentioning
confidence: 99%
“…Mud pumps are key facilities to compress low-pressure mud into high-pressure mud and are widely used in industrial manufacture, geological exploration, and energy power owing to their generality [1][2][3][4]. Mud pumps are the most important power machinery of the hydraulic pond-digging set during reclamation [5] and are major facilities to transport dense mud during river dredging [6]. During oil drilling, mud pumps are the core of the drilling liquid circulation system and the drilling facilities, as they transport the drilling wash fluids (e.g., mud and water) downhole to wash the drills and discharge the drilling liquids [7][8][9].…”
Section: Introductionmentioning
confidence: 99%